Eastern Promises: New Data on Chinese Loans in Africa, 2000 to 2014 - Deborah Brautigam; Jyhjong Hwang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
Chinese loan finance is often misunderstood in Africa. This paper provides an overview of a new database on Chinese loans and describes the research methodology for collecting this data. The authors report on the scale of these loans, their African recipients, and the sectors where borrowers are investing this finance. The paper also explains the Chinese system of securing risky loans with escrow accounts filled by exports and off-take arrangements. The data presented in this paper suggests that Chinese financiers have provided US86.3 billion to African governments and state-owned enterprises between 2000 and 2014. Yet the paper also warns that debt levels are rising, the Chinese are unlikely to cancel these debts, and there are concerns that African governments may not be able to absorb the sharply increased pledges made by Chinese leaders in December 2015.
Keywords: 330